Clinical Evaluation Methods for Flat Foot - Neha Mukkamala; Aishwarya Jain; Purvi Patel; G P Kumar (Achievements and Challenges of Medicine and Medical Science Vol. 9, 2024)
Flatfoot, also known as pes planus, is a condition marked by the lack or reduction of the medial longitudinal arch of the foot, which can lead to Osseo-ligamentous misalignment. This condition can be divided into two categories: flexible and rigid. The more prevalent form, flexible flatfoot, occurs when there is a normal arch in a non-weight-bearing position, but it flattens underweight, such as during standing or walking. While this condition may frequently show no symptoms, when they do arise, they may present as pain in the midfoot, heel, lower leg, knee, hip, or lower back. Individuals with flexible flatfoot tend to overpronate, which means their feet excessively roll inward, potentially leading to gait abnormalities and a higher susceptibility to injuries like ankle sprains. On the other hand, rigid flatfoot features a fixed and significantly lowered arch that stays flattened irrespective of weight-bearing, often accompanied by limited mobility in the foot. This type of flatfoot is more prone to causing ongoing discomfort and may be linked to underlying medical issues such as rheumatoid arthritis, neuropathy, or seronegative spondyloarthropathies. Various factors can lead to the onset of flatfoot, including genetic factors, past injuries to the foot or ankle, and certain health conditions such as obesity, diabetes, hypertension, or sensory neuropathies. Furthermore, individuals with a family history of flatfoot may have an increased likelihood of developing the condition. It is estimated that around 20% to 37% of the global population is affected by flat feet. Diagnostic methods like the plantar arch index, navicular drop test, Chippaux smirk index, and Staheli’s plantar arch index are convenient for identifying flat feet on a large scale.